Medical Insurance Representatives Perceptions on National Health Insurance Primary Healthcare Re-Engineering in South Africa: A Qualitative Study - Vivian Naidoo; Fatima Suleman; Varsha Bangalee (SAGE Publishing, 2024)
The South African government is moving toward universal health coverage (UHC) with the passing of the National Health Insurance (NHI) Bill. Access to quality primary healthcare (PHC) is the cornerstone of UHC principles. The South African governmental health department have begun focusing efforts on improving the efficiency and functionality of this system; that includes the involvement of private healthcare professionals and medical insurance companies. This study sought to explore perceptions of medical insurance company personnel on PHC re-engineering as part of NHI restructuring. A qualitative research design was adopted in this study. Semi-structured interviewed were conducted on 10 participants. Their responses were audio recorded and transcribed utilizing Microsoft Word ® documents. Nvivo ® was used to facilitate the analysis of data. A thematical approach was used to categories codes into themes. Although participants were in agreement with the current healthcare reform in South Africa. The findings of this study have highlighted several gaps in the NHI Bill at the current point in time. In order to achieve standardized quality of care at a primary level; it is imperative that reimbursement frameworks with clearly detailed service provision and accountability guidelines are developed.